2009
DOI: 10.4049/jimmunol.182.1.636
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Expression and Signaling of TLR4 and TLR9 in the Pathogenesis and Treatment of Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a common and often fatal inflammatory disorder affecting pre-term infants that develops upon interaction of indigenous bacteria with the premature intestine. We now demonstrate that the developing mouse intestine demonstrates reciprocal patterns of expression of TLR4 and TLR9, the receptor for bacterial DNA (CpGDNA). Using a novel ultrasound-guided in-utero injection system, we administered LPS directly into the stomachs of early and late gestation fetuses to induce TLR4 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
254
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(270 citation statements)
references
References 55 publications
15
254
1
Order By: Relevance
“…Toll-like receptor 9 is the receptor for bacterial DNA rich in CpG groups in enterocytes and in case of activation may lead to a decrease in TLR-4 signaling that is manifested by reduced cytokine production and decreased apoptosis. In fact, these findings may explain the protective effects of probiotics on NEC [34]. That is to say that these probiotics rich in bacterial DNA are expected to reduce TLR-4 signaling and the severity of NEC via activation of TLR-9 [35].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Toll-like receptor 9 is the receptor for bacterial DNA rich in CpG groups in enterocytes and in case of activation may lead to a decrease in TLR-4 signaling that is manifested by reduced cytokine production and decreased apoptosis. In fact, these findings may explain the protective effects of probiotics on NEC [34]. That is to say that these probiotics rich in bacterial DNA are expected to reduce TLR-4 signaling and the severity of NEC via activation of TLR-9 [35].…”
Section: Discussionmentioning
confidence: 91%
“…Recent evidence has shown that TLR-9, a homologue of TLR-4 and a receptor of bacterial DNA, may prevent exaggerated TLR-4 signaling [7,34]. Toll-like receptor 9 is the receptor for bacterial DNA rich in CpG groups in enterocytes and in case of activation may lead to a decrease in TLR-4 signaling that is manifested by reduced cytokine production and decreased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TLR9 recognises unmethylated CpG motifs in bacterial DNA and its signalling maintains the gut epithelial homeostasis by improving the barrier functions and by inducing tolerance towards other MAMP (16) . In utero the intestinal expression of TLR9 of mouse embryos decreases from days 14 to 18 and then increases again during the postnatal period (15) . Thus, it appears that a full-term newborn is programmed to receive TLR9 stimulation, which will improve the tolerance towards commensal bacteria.…”
Section: Prenatal Exposure To Microbes and Microbial Compoundsmentioning
confidence: 99%
“…This is supported by the study by Rautava et al where the presence of bacterial DNA, indicative for the presence of other MAMP too, in placenta and amniotic fluid was associated with the induction of expression profiles of TLR, especially TLR2 and TLR5 in fetal intestine (12) . Furthermore, the expression of different TLR, including TLR9, has been shown to change during the maturation of gut epithelial cells (14,15) . TLR9 recognises unmethylated CpG motifs in bacterial DNA and its signalling maintains the gut epithelial homeostasis by improving the barrier functions and by inducing tolerance towards other MAMP (16) .…”
Section: Prenatal Exposure To Microbes and Microbial Compoundsmentioning
confidence: 99%
“…It is currently thought that intestinal barrier disruption, a cardinal feature triggering NEC, is a toll-like receptor (TLR) 4-dependent phenomenon (36,37). Humans with NEC and rodent models of NEC both show elevated TLR4 expression that triggers enterocyte apoptosis and mucosal inflammation (38). EGF is highly abundant in both amniotic fluid as well as in breast milk; it inhibits TLR-4 signaling and prevents the development of NEC in animal models (39)(40)(41).…”
Section: Management Strategiesmentioning
confidence: 99%